PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN PERSEPSI DUKUNGAN ORGANISASI TERHADAP RETENSI KARYAWAN DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MEDIASI PADA GENERASI Z DAN MILENIAL - Muhammad Syukri Nasrul; Osly Usman (JURNAL LENTERA BISNIS, 2026)
The high turnover rate among young employees has become a strategic challenge for many organizations. This study examines the effects of transformational leadership and perceived organizational support on employee retention among Generation Z and Millennial employees, with job satisfaction as a mediating variable. The study employed a post-positivist quantitative-causal paradigm, with data collected from 150 respondents across public sector (ASN), private, and state-owned enterprise (BUMN) sectors in Jabodetabek using a five-point Likert scale instrument, and analyzed through PLS-SEM (SmartPLS 4). The findings reveal that: (1) transformational leadership has a significant positive effect on job satisfaction (β=0.551) and employee retention (β=0.396); (2) perceived organizational support positively affects job satisfaction (β=0.300) and employee retention (β=0.168); (3) job satisfaction positively affects employee retention (β=0.241); and (4) job satisfaction partially mediates the effects of transformational leadership (β=0.133; p=0.012) and perceived organizational support (β=0.072; p=0.041) on employee retention. These findings reinforce the integrative relevance of Social Exchange Theory, Self-Determination Theory, and Organizational Support Theory. Practically, organizations are recommended to strengthen transformational leadership competencies and design systematic organizational support programs as effective retention strategies for talented young employees.